Unusual Appearance of Multiple Exostosis: Case Report - Yalil Rodriguez; Aron Aliaga; Maria Eugenia Guerrero; David Aristizabal; Luis Arriola; Livia Zambrano (Cumhuriyet University, 2020)
Unilateral mandibular bone exostosis located in the buccal region is a rare condition. A 25-year-old female, who presented unilateral mandibular bone exostosis whose clinical diagnosis was confirmed using cone beam computed tomography. Additionally, a nodular torus palatinus was foud in the midline of the palate. Wear faces in the vestibular cusps of 46 as well as the thickening of the periodontal ligament space were present. Both are signs of occlusal trauma. The presence of mandibular tori could indicate other underlying conditions such as the presence of parafunctional activity or systemic health conditions. Mandibular exostosis can remain for life without needing to be surgically removed unless it compromises the prosthetic rehabilitation.